Photosensitizing systems based on alginate aerogels and methylene blue for controlled release of dye for antimicrobial photodynamic therapy - Shershnev, Ilya; Solovieva, Anna; Kopylov, Alexander; Cherkasova, Anastasiya; Kaplin, Vladislav; Rachev, Sergey; Kuryanova, Anastasiya; Aksenova, Nadezhda; Timofeeva, Victoriya; Akovantseva, Anastasiya; Zarkhina, Tatyana; Shantarovich, Viktor; et al. (Frontiers in Chemistry, 2025)
Photosensitizing systems based on methylene blue (MB)-loaded calcium alginate (CaA) and alginic acid (AA) aerogels were developed for photodynamic therapy of difficult-to-heal wounds. Hybrid aerogels incorporating polyvinylpyrrolidone (PVP, 2.5–40 wt%) into CaA and AA matrices were also made. The MB release kinetics in a phosphate buffer were found to depend on the aerogel type (AA or CaA). The incorporation of PVP increased the MB release rate by 1.5–2 times. The singlet oxygen (1O2) generation efficiency of MB embedded in the aerogels was influenced by their porosity and chemical composition. The activity of MB in the photogeneration of 1O2 increased by up to four times in the PVP-containing aerogels. Furthermore, the photoactivity of MB in the hybrid aerogel matrices significantly exceeded that in the single-component alginate aerogels.